Three-Dimensional Lattice Kinetic Scheme and Its Application to Simulate Incompressible Viscous Thermal Flows (Communications in Computational Physics, 2018)
In this paper, the three-dimensional lattice kinetic scheme is presented tosimulate incompressible viscous thermal flows. As compared with the standard LBM,the present scheme has the following good features. It can save the computer memory since there is no need to store the density distributions. Like the conventional NSsolvers, the implementation of boundary conditions is straightforward since the dependent variables are the macroscopic flow parameters. The easy implementation ofboundary conditions is a good property for solving three-dimensional flow problems.The present scheme is validated by simulating the three-dimensional natural convection in an air-filled cubical enclosure, which is heated differentially at two vertical sidewalls. The obtained numerical results compare very well with available data in theliterature.